2020
DOI: 10.1136/bmjopen-2019-033640
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for an international, multicentre stepped-wedge cluster randomised trial to evaluate the impact of a digital antimicrobial stewardship smartphone application

Abstract: IntroductionWith the widespread use of electronic health records and handheld electronic devices in hospitals, informatics-based antimicrobial stewardship interventions hold great promise as tools to promote appropriate antimicrobial drug prescribing. However, more research is needed to evaluate their optimal design and impact on quantity and quality of antimicrobial prescribing.Methods and analysisUse of smartphone-based digital stewardship applications (apps) with local guideline directed empirical antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…User experience was evaluated in an online questionnaire using LimeSurvey v2.06, an open-source online survey software. The questionnaire contained 23 questions and was developed by the authors based on interviews from a pilot study with an antibiotic stewardship app [ 21 ] and available literature [ 22 25 ]. In this pilot study 18 purposefully sampled potential users from several departments in three different countries (Sweden, Switzerland and The Netherlands) were interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…User experience was evaluated in an online questionnaire using LimeSurvey v2.06, an open-source online survey software. The questionnaire contained 23 questions and was developed by the authors based on interviews from a pilot study with an antibiotic stewardship app [ 21 ] and available literature [ 22 25 ]. In this pilot study 18 purposefully sampled potential users from several departments in three different countries (Sweden, Switzerland and The Netherlands) were interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review has shown that digital systems have been successful in reducing antimicrobial consumption, length of stay, mortality, and costs 62 . They can assist in appropriate selection of antimicrobial therapy, 70–72 recommending appropriate durations of treatment, 73 and to case find for stewardship interventions 74,75 . Bolt on systems can also be used to aid stewardship programs, providing features to document AMS interventions and reporting functionality for audit and local‐level surveillance 75,76 …”
Section: Digital Enablers For Afsmentioning
confidence: 99%
“…Since the overall methodological study quality varied considerably and comparison between studies was limited due to large variations in study design and outcome parameters, only cautious conclusions could be drawn. Currently, the impact of a smartphone app on antimicrobial prescribing by physicians in hospitals is being evaluated in an international randomized trial [53].…”
Section: Strengths and Limitationsmentioning
confidence: 99%